Anticardiolipin antibody in recurrent spontaneous aborting and fertile women - Couto, Egle; Barini, Ricardo; Silva, João Luiz Pinto e; Moraes, Denise Rocha Lima Pita de; Carvalho, Lucia Maria Fagian de (São Paulo Medical Journal, 1998)
OBJECTIVE: To determine the association between the presence of anticardiolipin antibody and a history of recurrent spontaneous abortion. STUDY DESIGN: clinical controlled study LOCATION: Department of Gynecology and Obstetrics - University of Campinas (UNICAMP) SUBJECTS: 52 individuals with recurrent spontaneous abortion were included in Group 1 and 104 individuals with at least one live born child in Group 2. Elapsed time from last delivery to blood sampling varied from six months to two years. METHOD: Between November 1993 and November 1994, patients’ blood samples were screened for anticardiolipin antibody by ELISA, as described by Triplett, Barna and Unger (1993). ANALYSIS: Chi-square and Fisher’s Exact tests were used for statistical analysis. Student’s "t" test was used to compare the means. RESULTS: There was no statistical difference in the presence of the anticardiolipin antibody between Group I (zero and 2.9%) and Group 2 (7.7 and 5.8%). CONCLUSION: There was no association between the presence of anticardiolipin antibody and recurrent spontaneous abortion.